ANALISIS PERLAKUAN AKUNTANSI ASET BIOLOGIS DANTANAMAN PRODUKTIF PADA PT ABC - Levana Virginia Winahyu, - (2019)
Biological assets are unique assets because these assets experience a biological transformation process. Because of the uniqueness, it causes biological assets require special treatment and using appropriate accounting methods, so that the company can determine the value of assets that describe the real condition of the company. This research took a research site at one of the plantation companies which listed on the IDX. When discussing biological assets in plantation companies, it will be directly related to bearer plants, so this study aims to find out how the accounting treatment of biological assets and bearer plants in PT ABC. The method used in this study is a qualitative method with ethnometodology approach. The results showed that PT ABC is guided by PSAK 69 and PSAK 16 in the recognition and measurement of biological asset and bearer plants. PSAK 69 is a new standard that began to be implemented by PT ABC since January 1, 2018 so that the implementation has not been perfect but it is good enough.